Charlotte Mew: melancholy poet - John Callender (BJPsych Bulletin, 2023)
Summary The main purpose of this article is to draw the attention of its readers to Charlotte Mew, a poet who is not well-known but whose work should be of great interest to mental health clinicians. She lived most of her life in the shadow of mental illness. Her poetry provides penetrating insights into her experiences of this in herself and in members of her family.